A Theoretical Framework for Evaluation of Musical Topics: The Case of Chopin - Zhou, Zhichao; Loo, Fung Chiat; Sze, Yeoh Joanne Pei (Harmonia: Journal of Arts Research and Education, 2025)
Peircean’ semiotics provides a cognitive framework for investigating the general process of thinking, expressed as a semiosis with multiple vectors. With their diverse expressions and connotations, musical topics inherently embody semiotic principles in musicological discourse, though debates persist regarding their semiotic references. This study presents a complementary model founded on Peirce’s tripartite semiotic framework in an attempt to account for the representation of musical topics and facilitate an approach to topical evaluation. Among other things, Peirce’s concept of correlates motivates the contemplation of topics with similar expressive qualities. In the process of unpacking, the paper considers the complex challenges and potential solutions to evaluating musical topics posed by their multiple referential layers. The analytical framework synthesizes Ratner’s rhetorical reduction approach to analyzing Romantic music with Grimalt’s topic categorization system. This approach is then applied to evaluate the nocturne topic in the secondary theme of the first movement of Chopin’s Piano Sonata No. 3 in B minor, with Chopin’s Barcarolle serving as a correlate to examine the effect of the nocturne topic. The semiotic-based topical evaluation demonstrates the effectiveness of this approach while raising critical awareness in topic theory discourse.